2011
DOI: 10.4149/neo_2011_04_352
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 polymorphisms and cervical cancer risk: A meta-analysis

Abstract: There were some studies on the associations between Glutathione S-transferase M1 (GSTM1) and Glutathione S-transferase T1 (GSTT1) polymorphisms and cervical cancer (CC) risk, but the results were inconsistent. Thus, a meta-analysis was performed.The electronic databases PubMed, Science Direct, CBM, and CNKI were searched for possible studies. Finally, 16 studies (1,627 cases and 2,161 controls) were included. For the GSTM1 and GSTT1 polymorphisms, the unadjusted odds ratios (OR) and 95% confidence intervals (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Zhuo et al [63] found that GSTM1 null genotype significantly increased susceptibility to oral cancer among Asians, but not Caucasians. Wang et al [64] reported that the null genotype of GSTM1 was a risk factor in cervical cancer among Asians, but not Caucasians. A recent study by Wang et al [65] showed that an increased hepatocellular carcinoma risk was significantly affected by the null genotype of GSTM1 among Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Zhuo et al [63] found that GSTM1 null genotype significantly increased susceptibility to oral cancer among Asians, but not Caucasians. Wang et al [64] reported that the null genotype of GSTM1 was a risk factor in cervical cancer among Asians, but not Caucasians. A recent study by Wang et al [65] showed that an increased hepatocellular carcinoma risk was significantly affected by the null genotype of GSTM1 among Asians.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, GSTM1 deletions have been linked to osteosarcoma incidence [71] and recurrence [72], with a non-statistically significant positive association with soft tissue sarcoma mortality [73]. Other studies of GSTM1 deletions have identified positive associations between the null genotype and a variety of cancers, included oral [45], colorectal [74], cervical [75], and bladder [76].…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of modified enzymatic activity that predisposes susceptibility to several cancers including carcinoma of skin [5], pancreas [7], liver [13], ovary [14], bladder [15], lung [16], breast [17], head and neck [18], cervix [19], and prostrate [20].This study was designed to investigate the association of GSTM1 and GSTT1 polymorphisms with cervical cancer and to estimate the clinical impact of these polymorphisms in the progression of SCCA.…”
Section: Introductionmentioning
confidence: 99%